Joubert syndrome in two sibs and the differential diagnosis of cerebellar vermian dysgenesis - (:unkn) unknown (My University, 1997)
We present two siblings with Joubert syndrome. Malformation of the cerebellar vermis, abnormal eye movements, developmental delay and retinitis pigmentosa are described. The differential diagnosis of vermian dysgenesis is discussed. At present the genes for Joubert syndrome and the overlap syndromes are not identified and the differential diagnosis of these syndromes is not possible by molecular genetic methods. Therefore the clinical and neuroradiological overlap with other syndromes should be recognized.
Keywords: Hypo/aplasia of cerebellar vermis; Joubert syndrome; Overlap syndromes